Gold phenolate complexes: synthesis, structure, and reactivity - Ibrahim, Nada; Larsen, Mie Højer; Pernpointner, Markus; Rominger, Frank; Hashmi, A. Stephen K. (Organometallics, 2013)
Seven different NHC gold(I) phenolate complexes were synthesized. Structural data, including X-ray crystal structure analyses, could be obtained for each of them. An investigation by computational chemistry, including NBO analysis, indicates three-center-four-electron hyperbonds among the carbene carbon, the gold atom, and the oxygen atom of the phenolate with an approximate 60:40 distribution of the bonding interaction in favor of the carbene-gold bond. The new class of complexes shows only moderate catalytic activity.
Gesehen am 07.12.2021